2020
DOI: 10.1007/s10668-020-01031-2
|View full text |Cite
|
Sign up to set email alerts
|

Time–frequency co-movement between COVID-19, crude oil prices, and atmospheric CO2 emissions: Fresh global insights from partial and multiple coherence approach

Abstract: This paper endeavors to analyze and provide fresh global insights from the asymmetric nexus between the recent outbreak of COVID-19, crude oil prices, and atmospheric CO 2 emissions. The analysis employs a unique Morlet's wavelet method. More precisely, this paper implements comprehensive wavelet coherence analysis tools, including continuous wavelet coherence, partial wavelet coherence, and multiple wavelet coherence to the daily dataset spanning from December 31, 2019 to May 31, 2020. From the frequency pers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 35 publications
1
21
1
Order By: Relevance
“…Several statistical and scientific models are employed to examine the relations among Covid-19, meteorological factors, and air pollutants, for instance, the generalized additive model (GAM) (Xie and Zhu 2020;Zhu et al 2020b;Liu et al 2020), M-SEIR model (Shi et al 2020), and AERMOD (Sharma et al 2020d (Zoran et al 2020; Briz-Redón and Serrano-Aroca 2020), quantile-on-quantile approach , and wavelet approach Iqbal et al 2020;Habib et al 2020). Shi et al (2020) use the M-SEIR model to explain no significant association between humidity and Covid-19.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Several statistical and scientific models are employed to examine the relations among Covid-19, meteorological factors, and air pollutants, for instance, the generalized additive model (GAM) (Xie and Zhu 2020;Zhu et al 2020b;Liu et al 2020), M-SEIR model (Shi et al 2020), and AERMOD (Sharma et al 2020d (Zoran et al 2020; Briz-Redón and Serrano-Aroca 2020), quantile-on-quantile approach , and wavelet approach Iqbal et al 2020;Habib et al 2020). Shi et al (2020) use the M-SEIR model to explain no significant association between humidity and Covid-19.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Covid-19 not only is a serious concern for public health but also caused has a devastating socio-economic situation in the countries it invaded (Raza et al 2020;Chakraborty and Maity 2020;Habib et al 2020). The developing countries categorized by the slow growth rate, poor healthcare infrastructure, and large population (a majority of them living in extreme poverty) have been severely affected by the Covid-19 pandemic (Sharma et al 2020b, c).…”
Section: Introductionmentioning
confidence: 99%
“…Habib et al [44] analyse asymmetric links between the COVID-19 outbreak, oil prices, and atmospheric CO 2 emissions. They use the unique Morlet's wavelet method in the analysis.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The recent Sars-CoV-19 pandemic has shown how different the vision can be between an economic point of view and a biophysical point of view as also Habib et al ( 2020 ) and Albulescu ( 2020 ) have shown. During the global lockdown, with a worldwide economy frozen, the oil price—I take Brent as an example—fell, in April 2020, to 18.47 $/barrel (source: Europe Spot Brent Price crude oil), with an average decrease of − 34% compared to the previous year (the average values of the prices went from 64.35 $/barrel to 41.70 $/barrel).…”
Section: Introductionmentioning
confidence: 98%